Seasonal Variation in Biochemical Composition of Edible Oyster (Saccostrea cucullata) from Indian Sundarbans - Mitra, Abhijit; Basu, Shibdas; Banerjee, Kakoli (Fishery Technology, 2025)
Protein, lipid, glycogen, moisture and ash content of the edible oyster species were analysed on monthly basis during 2004 and 2005 from the cultured site at Chotomollakhaliin eastern sector of Indian Sundarbans. The culture of edible oyster was initiated in this part of the country in order to provide alternative livelihood to the poverty stricken population in the Indian Sundarbans, which may otherwise, lead to destruction of natural resources of this mangrove ecosystem. Simultaneous monitoring of hydrological parameters (surface water temperature, salinity, pH, nitrate, phosphate and silicate) and phytopigment level of theambient water was also carried out in this cultured site to investigate the interrelationship between the hydrological parameters and biochemical composition of the oyster tissue. The two year study indicates significant seasonal oscillation of the major biochemical constituents of the oyster